Method for synthesizing mullite porous ceramic catalyst carrier by using solid waste

By adjusting the ratio of aluminum, silicon and heteroatoms and calcining at high temperatures, a mullite porous ceramic catalyst with high porosity and efficient catalysis is generated, the problems of low porosity and low compressive strength of existing catalysts are solved, and a more efficient catalytic effect is achieved.

CN119504282APending Publication Date: 2025-02-25PINGXIANG QUNLI IND FILLING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411436998.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing mullite porous ceramic catalysts have problems such as low porosity, low compressive strength and low catalytic efficiency.

Method used

By mixing aluminum ash, fly ash and dehydrated sludge, adjust the weight ratio of aluminum:silicon: heteroatoms, and add water, fatty alcohol polyoxyethylene ether sodium sulfate, magnesium oxide, sodium fluoride and other substances. After drying and high-temperature calcination, a high-porosity mullite porous ceramic catalyst is generated and loaded with 5% V active components.

Benefits of technology

The resulting catalyst has high porosity, strong compressive strength and efficient catalytic properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention aims to provide a method for synthesizing a mullite porous ceramic catalyst carrier by using solid wastes, which comprises the following steps: S1, mixing aluminum ash, fly ash and dewatered sludge, so that the weight ratio of aluminum to silicon to heteroatoms is (3-4): (2-3): (0.3-0.6), the heteroatoms comprise one or more of iron, manganese, nickel, copper and chromium coexist, and the weight ratio of the aluminum ash to the fly ash to the dewatered sludge is (3-4): (2-3): (0.3-0.6); mixing the mixture in a ball mill; s2, putting water, fatty alcohol polyoxyethylene ether sodium sulfate, magnesium oxide, sodium fluoride and the like into the mixture obtained in the step S1 according to the proportion of 90: 5: 0: 5, and putting all experimental raw materials into a ball mill for ball milling. And calcining the dried ceramic in a high-temperature box-type furnace. The catalyst prepared from the obtained porous ceramic has a good denitration effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for producing a catalyst, in particular to a method for synthesizing a mullite porous ceramic catalyst carrier by using solid waste. Background Art

[0002] Under the environment of rapid development of the world economy, global industry has also developed rapidly, and the problems of environmental protection and resource conservation have become increasingly prominent. Therefore, it is particularly important to adjust the contradictory relationship between the porosity and mechanical properties of products, improve the thermal shock resistance and oxidation resistance of porous ceramic materials to increase the service life of products, and reduce the temperature required for experiments. Mullite porous ceramic materials are new materials that meet the needs of this development. At the same time, they have excellent characteristics such as good mechanical properties, high temperature resistance, and corrosion resistance, which are of great help to environmental protection, resource conservation, and efficiency improvement.

[0003] Mullite (or monetite, Aluminum silicate) refers to a series of minerals composed of aluminum silicates. It is worth mentioning that SiO2-Al2O3 system is the most important binary system in ceramics. Since the first mullite phase diagram published in 1909, more than a dozen different phase diagrams have been published. The focus of the debate is whether the intermediate phase mullite is a stable compound or an unstable compound. Later, the issue was unified. The composition of mullite is not fixed, and its alumina content fluctuates between 72% and 78%.

[0004] The existing catalyst prepared by using mullite as a carrier also has the problems of low porosity, low compressive strength, low density and low catalytic efficiency. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a method for synthesizing a mullite porous ceramic catalyst carrier using solid waste. The catalyst obtained by this method has high porosity, high compressive strength and high catalytic efficiency.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramic obtained by drying the ceramic slurry in step S2 is placed in a high temperature box furnace for calcination at 1200°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

[0007] 4) The porous ceramics obtained in step 3) were loaded with 5% V to prepare porous ceramic catalysts Preferably, step S1 is specifically to mix aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum:silicon:heteroatoms is (3-4):(2-3):(0.3-0.6), wherein the heteroatoms include: one or more of iron, manganese, nickel, copper and chromium, and the mixture is mixed in a ball mill for 2-4 hours.

[0008] Preferably, the step S2 specifically comprises adding water, sodium fatty alcohol polyoxyethylene ether sulfate, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and milling the mixture in a ball mill for 2-4 hours to obtain a ceramic slurry.

[0009] Preferably, the step 3) is specifically to place the solid obtained in step S2 into a high temperature box furnace for calcination at 1200°C. The sintering system is: heating up to 700°C at a heating rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling with the furnace.

[0010] Preferably, the step 4) is specifically to load 5% of V on the porous ceramic obtained in step 3) to prepare a porous ceramic catalyst.

[0011] Beneficial effects: The invention discloses a method for synthesizing a mullite porous ceramic catalyst carrier using solid wastes. The method comprises the following steps: aluminum ash, fly ash and dewatered sludge are mixed to make the weight ratio of aluminum: silicon: heteroatom be (3-4): (2-3): (0.3-0.6); water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide and sodium fluoride are then added; the mixture is dried and calcined to generate a high-porosity catalyst in the mullite. The catalyst has high compactness and high compressive strength; and the catalyst formed by loading V has a better catalytic effect. DETAILED DESCRIPTION

[0012] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0013] Example 1 A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramic obtained by drying the ceramic slurry in step S2 is placed in a high temperature box furnace for calcination at 1200°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

[0014] 4) The porous ceramics obtained in step 3) were loaded with 5% V to prepare porous ceramic catalysts.

[0015] Example 2 A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramic obtained by drying the ceramic slurry in step S2 is placed in a high temperature box furnace for calcination at 1300°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

[0016] 4) The porous ceramics obtained in step 3) were loaded with 5% V to prepare porous ceramic catalysts.

[0017] Example 3 A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramics obtained by drying the ceramic slurry in step S2 are placed in a high temperature box furnace for calcination at 1500°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

[0018] 4) The porous ceramics obtained in step 3) were loaded with 5% V to prepare porous ceramic catalysts.

[0019] Example 4 A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramics obtained by drying the ceramic slurry in step S2 are placed in a high temperature box furnace for calcination at 1600°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

[0020] 4) The porous ceramics obtained in step 3) were loaded with 5% V to prepare porous ceramic catalysts.

[0021] Example 5 A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramic obtained by drying the ceramic slurry in step S2 is placed in a high temperature box furnace for calcination at 1450°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

[0022] 4) The porous ceramics obtained in step 3) were loaded with 5% V to prepare porous ceramic catalysts.

[0023] Example 6 A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:1:8:1 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramic obtained by drying the ceramic slurry in step S2 is placed in a high temperature box furnace for calcination at 1450°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

[0024] 4) The porous ceramics obtained in step 3) were loaded with 5% V to prepare porous ceramic catalysts.

[0025] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the ceramic body is placed in a high-temperature box furnace at 1450° C. for 1 h for calcination. Other preparation methods and conditions are consistent with those of Example 1.

[0026] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the ceramic body is placed in a high-temperature box furnace at 1450° C. for 2 h for calcination. Other preparation methods and conditions are consistent with those of Example 1.

[0027] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the ceramic body is placed in a high-temperature box furnace for calcination at 1450° C. for 4 h. Other preparation methods and conditions are consistent with those of Example 1.

[0028] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the ceramic body is placed in a high-temperature box furnace for calcination at 1450° C. for 5 h. Other preparation methods and conditions are consistent with those of Example 1.

[0029] Comparative Example 5 The only difference between Comparative Example 5 and Example 5 is that water, sodium fatty alcohol polyoxyethylene ether sulfate, magnesium oxide, sodium fluoride, etc. are added to the mixture in a ratio of 90:4:2:4, and the other preparation methods and conditions are consistent with Example 5.

[0030] Comparative Example 6 The only difference between Comparative Example 6 and Example 5 is that water, sodium fatty alcohol polyoxyethylene ether sulfate, magnesium oxide, sodium fluoride, etc. are added to the mixture in a ratio of 90:2:6:2, and the other preparation methods and preparation conditions are consistent with Example 5.

[0031] Comparative Example 7 The only difference between Comparative Example 7 and Example 6 is that 1% of V is loaded on the porous ceramic, and the other preparation methods and conditions are consistent with those of Example 6.

[0032] Comparative Example 8 The only difference between Comparative Example 8 and Example 6 is that 3% of V is loaded on the porous ceramic, and the other preparation methods and conditions are consistent with those of Example 6.

[0033] For Examples 1-5 and Comparative Examples 1-6, the pore size and porosity were measured. The measurement results are shown in Appendix 1.

[0034] Table 1 Aperture (mm) Porosity (%) Example 1 0.1-0.3 67.6 Example 2 0.1-0.3 59.7 Example 3 0.1-0.3 68.3 Example 4 0.1-0.3 81.3 Example 5 0.1-0.3 59.5 Example 6 0.1-0.3 85 Comparative Example 1 0.1-0.3 74.5 Comparative Example 2 0.1-0.3 73.4 Comparative Example 3 0.1-0.3 82.9 Comparative Example 4 0.1-0.3 80.1 Comparative Example 5 0.1-0.3 77.8 Comparative Example 6 0.1-0.3 80 For Example 6 and Comparative Examples 7-8, the denitrification effect at 350°C was measured. The results are shown in Table 2. Table 2 Active ingredient content (%) Catalytic efficiency (%) Example 6 5 93.6 Example 7 1 59.7 Example 8 3 68.3 Same mass TiO2 5 89.7 By embodiment 1-4, comparative example 1-4 is compared and can be seen that by the present invention, when the sintering temperature is increased, the material transfer in the sintering reaction is promoted, and the formation of the mullite phase in the sintering reaction is promoted. The content of the generated mullite phase increases and changes from a sheet to a needle-like and prism-like shape with good mechanical properties. The densification degree of the mullite porous ceramic sample is improved, and the porosity of the mullite porous ceramic sample is reduced, and the strength of the mullite porous ceramic sample is increased accordingly. At the same time, when the temperature during the sintering of the mullite porous ceramic is increased, the pore size distribution of the mullite porous ceramic sample changes less and remains basically unchanged. The pore size range is mainly distributed between 0.1-0.2mm and 0.2-0.3mm. Extending the sintering time is conducive to the material transfer in the sintering reaction, and the formation of the mullite phase in the sintering reaction is promoted. The amount of mullite phase generated increases, the densification degree of the mullite porous ceramic sample is improved, the porosity changes less, and the compressive strength increases.

[0035] From Example 6 and Comparative Examples 5-6, it can be seen that when MgO is gradually added to the mullite porous ceramic sample, the amount of mullite phase generated in the sample increases, the porosity gradually decreases, the sample shrinkage increases, the degree of structural densification increases, and the compressive strength gradually increases. At the same time, as the amount of MgO added gradually increases, the degree of structural densification increases.

[0036] By comparing Example 6, Comparative Examples 7-8 and catalysts of the same mass of TiO2, it can be seen that the catalytic efficiency increases with the increase of the V active component. Similarly, the catalytic effect of the active component loaded on the porous ceramic is better than that of TiO2.

[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for synthesizing a mullite porous ceramic catalyst carrier using solid waste, characterized in that: The method comprises the following steps: S1: mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom includes one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours; S2: adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. in a ratio of 90:5:0:5 into the mixture obtained in step S1 and ball milling in a ball mill for 2-4 hours to obtain a ceramic slurry; S3: The ceramic obtained by drying the ceramic slurry in step S2 is placed in a high temperature box furnace for calcination at 1200°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.

2. The method according to claim 1, characterized in that: Specifically, step S1 comprises mixing aluminum ash, fly ash and dewatered sludge so that the weight ratio of aluminum: silicon: heteroatom is (3-4): (2-3): (0.3-0.6), wherein the heteroatom comprises one or more of iron, manganese, nickel, copper and chromium, and mixing the mixture in a ball mill for 2-4 hours.

3. The method according to claim 1, characterized in that Specifically, step S2 includes adding water, sodium sulfate of fatty alcohol polyoxyethylene ether, magnesium oxide, sodium fluoride, etc. into the mixture obtained in step S1 in a ratio of 90:5:0:5, and milling the mixture in a ball mill for 2-4 hours.

4. The method according to claim 1, characterized in that Specifically, the ceramic obtained by drying the ceramic slurry in step S2 is placed in a high-temperature box furnace for calcination at 1200°C. The sintering schedule is: heating up to 700°C at a rate of 5°C / min, stabilizing for 2h, then heating up to a predetermined temperature at a rate of 10°C / min, sintering for 2h, and then cooling in the furnace.